The Role of Learning Motivation in Mediating Student Learning Outcomes - Widiyanti, Anik; Widodo, Joko; Rozi, Fahrur (Universitas Negeri Semarang, 2024)
Learning outcomes are successes achieved by students in the learning process which are manifested in the form of numbers. The purpose of this study is to analyze the direct and indirect influence of digital literacy, technological equipment on learning outcomes through learning motivation. Quantitative research using questionnaires as a data collection instrument. The population was 178 students majoring in MPLB at SMK N Business Management in Semarang City. The sample size was 123 students using the Slovin formula. The sampling technique uses Proportional Random Sampling. Data analysis techniques use descriptive statistical analysis, path analysis, and sobel tests. The results show digital literacy, technological equipment, learning motivation directly affect learning outcomes. Digital literacy does not have a direct effect on learning motivation, technology equipment has a direct effect on learning motivation. Digital literacy does not indirectly affect learning outcomes through learning motivation, technological equipment indirectly affects learning outcomes through learning motivation. The conclusion is the role of learning motivation in educating digital literacy and technological equipment is partial mediation. The advice in this study is for students to be able to motivate themselves in improving digital literacy in facing an independent learning curriculum to improve learning outcomes.